Use of High Sensitivity Cardiac Troponin as An Early Diagnosis of Acute Myocardial Infarction (IMA): Systematic Review - Purwanti Nurfita Sari; Abu Bakar; Laily Hidayati (Indonesian Journal of Global Health Research, 2025)
Acute myocardial infarction (IMA) is a leading cause of morbidity and mortality worldwide, so early diagnosis is needed to detect the disease. High sensitivity troponin assessment is a biomarker examination that can diagnose Acute Myocardial Infarction. The purpose of this study is to determine the effectiveness of the use of High Sensitivity Cardiac Troponin and as an early diagnosis of Acute Myocardial Infarction (IMA). This study is a systematic review study of 4 databases, namely Scopus, PubMed, EBSCO Host, and Sage Journals, with the keywords "high sensitivity cardiac troponin" AND "acute myocardial infarction". The results of the study followed the protocol and rules of Preferred Reporting Items for Systematic Reviews (PRISMA) and used the JBI tool to assess the quality of the articles to be analyzed. The inclusion criteria in this study are articles taken in the last 5 years using the Randomized Control Trials (RCT) method and observational studies. A literature search yielded 452 research articles, of which 10 were included after several selections in a systematic review and were eligible for analysis. The ten articles used random comparison and observation research methods. All articles show that high sensitivity cardiac troponin has high sensitivity and specificity in supporting the diagnosis of acute myocardial infarction. This shows that high sensitivity cardiac troponin is one of the biomarker examinations that has high sensitivity in identifying patients with a high risk of acute myocardial infarction. This finding is expected to be a reference for health workers to determine the initial diagnosis of Acute Myocardial Infarction (IMA).